Ethnomatematics in Mathematics Learning in Primary Schools: A Systematic Literature Review - Nurhaswinda, Nurhaswinda; Nusantara, Toto; Masfufah, Aynin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The culture that develops in society can be used as material for mathematics learning in elementary schools. This scientific paper was written using the Systematic Literature Review (SLR) methodology. SLR is a method for identifying, reviewing, and summarizing multiple studies on a specific topic. The reviewed articles include a total of 210 articles on ethnomathematics in elementary school mathematics education, collected from the Perpusnas database, Publish or Perish, Google Scholar, and Scopus over the past 10 years. For the SLR, 4 articles were used. The results of the literature review indicate that ethnomathematics is a discipline that can be applied in mathematics education in elementary schools. This is evidenced by research showing that ethnic mathematics can improve students' skills in the learning process, especially for children in elementary schools. Many cultural variations can be represented in ethnomathematics, such as traditional games, building structures, cuisine, and traditional activities found in villages. By integrating ethnomathematics into mathematics education in elementary schools, it is hoped that students can develop a deeper understanding of mathematics, strengthen their cultural identity, and appreciate cultural diversity.Keywords. Etnomatematika, Matematika, Sekolah Dasar